Flow Characteristics of Bulb Tubular Turbine Based on Solid-liquid Two-phase Flow Model - Q. Li; F. Zhou; Q. Wang (Journal of Applied Fluid Mechanics)
This study examines the operational efficiency of a bulb tubular turbine under solid-liquid two-phase (SLTP) flow conditions. By employing the Euler-Euler method, the characteristics of SLTP flow in the turbine with different solid particle diameters were analyzed. The research findings demonstrate that the increase in solid particle diameter from 0.01 mm to 0.15 mm decreases the maximum liquid phase velocity in the XY plane by approximately 0.26%. The introduction of solid particles results in increased likelihood of cavitation and vortices in the draft tube region, leading to diminished energy recovery efficiency in this area. Within the impeller domain, regions with high solid particle concentration are predominantly located on the blade front hub and inlet edge, while the blade's rear side exhibits an overall higher concentration. Further analysis reveals a positive correlation between blade velocity/concentration distribution and the diameter of solid particles. Furthermore, particle size has a significant impact on the solid phase trajectory and solid phase velocity in the draft tube area. Particles with larger diameters tend to move in more irregular and chaotic patterns, promoting the formation of vortices in the draft tube region. Notably, while the velocity of the solid phase at the draft tube inlet decreases with increasing particle size, the velocity fluctuations within the draft tube become more pronounced. Among the different flow components of the hydraulic turbine, the wear severity follows a descending order: the blade region experiences the highest wear, followed by the runner chamber, guide vane area, and draft tube region. Additionally, the diameter of the solid phase shows a positive correlation with both the wear area and the maximum wear rate in the runner chamber, blade region, and guide vane area, whereas it demonstrates a negative correlation with wear in the draft tube region.